Effect of walking on sand on co-Contraction of the lower limb muscles in individuals with overpronated foot - Amir Fatollahi; AmirAli Jafarnezhadgero; Nasrin Amirzade (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Foot pronation is in the open kinetic chain composed of eversion, abduction, and ankle dorsiflexion. Foot overpronation may be associated with different lower limb injuries. The purpose of this study was to investigate the effect of walking on the sand on co-Contraction of the lower limb muscles in individuals with overpronated foot. Methods: The present study was a semi-experimental and laboratory type. Thirty healthy individuals and 30 individuals with foot overpronation volunteered to participate in this study. Muscle activity was recorded by an 8-channel electromyography system with a surface electrode during walking on sand. Two-way ANOVA test was used for statistical analysis at the significant level P<0/05. Results: The results demonstrated lower ankle-directed co-Contraction during walking on sand compared with walking on level ground (P<0/001). Other components of ankle-directed co-Contraction did not demonstrate any significant differences between walking on sand compared with walking on level ground (P>0/05). Conclusion: Individuals with overpronated foot demonstrated lower ankle-directed co-Contraction during walking on sand compared with walking on stable level ground. Individuals with overpronated foot showed a greater ankle-directed co-Contraction than the healthy group. Decreased ankle-directed co-Contraction indicated a positive effect of walking on sand in individuals with foot overpronation.